Computer‐generated reminders delivered on paper to healthcare professionals: effects on professional practice and healthcare outcomes - Arditi, Chantal (Cochrane Database Syst Rev, 2017)
BACKGROUND: Clinical practice does not always reflect best practice and evidence, partly because of unconscious acts of omission, information overload, or inaccessible information. Reminders may help clinicians overcome these problems by prompting them to recall information that they already know or would be expected to know and by providing information or guidance in a more accessible and relevant format, at a particularly appropriate time. This is an update of a previously published review. OBJECTIVES: To evaluate the effects of reminders automatically generated through a computerized system (computer‐generated) and delivered on paper to healthcare professionals on quality of care (outcomes related to healthcare professionals' practice) and patient outcomes (outcomes related to patients' health condition). SEARCH METHODS: We searched CENTRAL, MEDLINE, Embase, six other databases and two trials registers up to 21 September 2016 together with reference checking, citation searching and contact with study authors to identify additional studies. SELECTION CRITERIA: We included individual‐ or cluster‐randomized and non‐randomized trials that evaluated the impact of computer‐generated reminders delivered on paper to healthcare professionals, alone (single‐component intervention) or in addition to one or more co‐interventions (multi‐component intervention), compared with usual care or the co‐intervention(s) without the reminder component. DATA COLLECTION AND ANALYSIS: Review authors working in pairs independently screened studies for eligibility and abstracted data. For each study, we extracted the primary outcome when it was defined or calculated the median effect size across all reported outcomes. We then calculated the median improvement and interquartile range (IQR) across included studies using the primary outcome or median outcome as representative outcome. We assessed the certainty of the evidence according to the GRADE approach. MAIN RESULTS: We identified 35 studies (30 randomized trials and five non‐randomized trials) and analyzed 34 studies (40 comparisons). Twenty‐nine studies took place in the USA and six studies took place in Canada, France, Israel, and Kenya. All studies except two took place in outpatient care. Reminders were aimed at enhancing compliance with preventive guidelines (e.g. cancer screening tests, vaccination) in half the studies and at enhancing compliance with disease management guidelines for acute or chronic conditions (e.g. annual follow‐ups, laboratory tests, medication adjustment, counseling) in the other half. Computer‐generated reminders delivered on paper to healthcare professionals, alone or in addition to co‐intervention(s), probably improves quality of care slightly compared with usual care or the co‐intervention(s) without the reminder component (median improvement 6.8% (IQR: 3.8% to 17.5%); 34 studies (40 comparisons); moderate‐certainty evidence). Computer‐generated reminders delivered on paper to healthcare professionals alone (single‐component intervention) probably improves quality of care compared with usual care (median improvement 11.0% (IQR 5.4% to 20.0%); 27 studies (27 comparisons); moderate‐certainty evidence). Adding computer‐generated reminders delivered on paper to healthcare professionals to one or more co‐interventions (multi‐component intervention) probably improves quality of care slightly compared with the co‐intervention(s) without the reminder component (median improvement 4.0% (IQR 3.0% to 6.0%); 11 studies (13 comparisons); moderate‐certainty evidence). We are uncertain whether reminders, alone or in addition to co‐intervention(s), improve patient outcomes as the certainty of the evidence is very low (n = 6 studies (seven comparisons)). None of the included studies reported outcomes related to harms or adverse effects of the intervention. AUTHORS' CONCLUSIONS: There is moderate‐certainty evidence that computer‐generated reminders delivered on paper to healthcare professionals probably slightly improves quality of care, in terms of compliance with preventive guidelines and compliance with disease management guidelines. It is uncertain whether reminders improve patient outcomes because the certainty of the evidence is very low. The heterogeneity of the reminder interventions included in this review also suggests that reminders can probably improve quality of care in various settings under various conditions.